Analysis of the Skid Resistance Decrease in Bituminous Pavements in Dual-Carriageway Tunnels - Heriberto Pérez-Acebo; Miren Isasa; Itziar Gurrutxaga; Ángela Alonso-Solórzano (Buildings)
Unlike other pavement indices, the skid resistance, or friction, of bituminous pavements behaves differently. After the extension of a new layer, the friction increases as the bitumen film is removed and the aggregates are exposed. The aggregates are then polished by traffic, mainly by heavy vehicles, and the pavement reaches the seasonal phase, in which, if heavy traffic volume remains constant, the only variations are seasonal, with maximum values in winter and minimum values in summer. Nonetheless, in tunnels, as they are not exposed to climatic actions, the friction value is lower than outside. Therefore, the article evaluates the skid resistance decrease in tunnels compared to outdoor conditions. For this purpose, the skid resistance values in dual-carriageway tunnels in Gipuzkoa (Spain) were studied and compared with the values obtained 500 m before and after the tunnel. Overall, a 10% friction decrease was observed inside the tunnels. In winter, the decrease was 11%, while in summer it was 8%. In tunnels longer than 500 m, the decrease was greater (12%) than in tunnels shorter than 500 m (9% and 7%). This analysis contributes to a better knowledge of the available friction inside a tunnel and to the better management of road safety.